Biocompatible therapeutic albumin/genipin bioglue for postoperative wound adhesion and residual tumor ablation. (December 2021) - Wang, Yaqiong; Guo, Jingjing; Li, Bingjie; Li, Dong; Meng, Zhaowei; Sun, Shao-Kai
Abstract: Surgical adhesives have partly replaced traditional sutures to seal and reattach tissues due to their superiorities in preventing liquids leakage and avoiding secondary damage in the surrounding wound area. Most of the existing adhesives are committed to promoting wound healing and functional recovery. A therapeutic adhesive that assists in clearing the residual tumors in the surgical area is undoubtedly meaningful to obtain a better clinical outcome. Herein, enlightened by commercial BioGlue (albumin/glutaraldehyde sealant), a biocompatible therapeutic albumin/genipin bioglue is designed for postoperative wound adhesion and tumor ablation. The albumin/genipin bioglue is formed by simple mixing of bovine serum albumin (BSA) and genipin (GP) under a 35 °C water bath for 24 h without further purification. The obtained dark-blue fluorescent adhesive exhibits a significant temperature increase accompanied by heating-induced curing once irradiated with an 808-nm laser. This unique characteristic allows BSA-GP a therapeutic adhesive for postoperative wound adhesion and photothermal elimination of residual tumors under laser irradiation. Moreover, its easy injectability and impressive photothermal efficacy also make it feasible for in situ tumor photothermal ablation. The ultrasimple synthetic strategy by mimicking BioGlue endows BSA-GP adhesive with large-scale production capacity and clinical transformation potential, which is a successful paradigm for reforming existing clinical products. Graphical abstract: Inspired by albumin glutaraldehyde tissue adhesive (BioGlue), a therapeutic adhesive is one-step crosslinked by bovine serum albumin (BSA) and genipin (GP). The BSA-GP adhesive as a therapeutic adhesive could realize postoperative wound closure and residual cancers ablation owing to its near-infrared-induced curing and adhesive properties and photothermal effect. Moreover, its easy injectability and impressive photothermal efficacy also make it feasible for in situ tumor photothermal therapy. This design shows bright enlightenment in reforming existing clinical products, improving their biocompatibility, and exploring their new biological application. Image 1